2022
DOI: 10.1002/jwmg.22198
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting searcher efficiency and scavenger removal of bat carcasses in Neotropical wind facilities

Abstract: Bat fatalities at wind facilities have been reported worldwide, and environmental impact assessments depend on searches for carcasses around wind turbines to quantify impacts. Some of the carcasses may go undetected by search teams or be removed by scavengers during search intervals, so these biases must be evaluated and taken into account in fatality estimation. We investigated the influence of different factors on searcher efficiency and scavenger removal in a dry forest area in northeastern Brazil, one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…We estimated searcher efficiency with fresh brown mice carcasses (Myodes glareolus, Cricetidae, Rodentia), obtained from a seminatural population at a facility where they were maintained under veterinarian control. We considered mice carcasses as suitable surrogates of bat carcasses because previous studies in Europe showed that the persistence time and detection probability of carcasses is similar in these taxa (Niermann et al, 2011;Barros et al, 2022). At each of the turbines, one of us placed 10 mice carcasses in a random design.…”
Section: Searcher Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated searcher efficiency with fresh brown mice carcasses (Myodes glareolus, Cricetidae, Rodentia), obtained from a seminatural population at a facility where they were maintained under veterinarian control. We considered mice carcasses as suitable surrogates of bat carcasses because previous studies in Europe showed that the persistence time and detection probability of carcasses is similar in these taxa (Niermann et al, 2011;Barros et al, 2022). At each of the turbines, one of us placed 10 mice carcasses in a random design.…”
Section: Searcher Efficiencymentioning
confidence: 99%
“…For example, Rydell et al (2010) reported that 1.3 (median; range 0-41) carcasses were documented per wind turbine and year in Central Europe (Germany, Switzerland, and Austria). But Many carcasses are not found by searchers because the small size of animals impairs the detection probability (Niermann et al, 2011;Barros et al, 2022), particularly when the search area consists of a heterogeneous surface or when vegetation is high. Also, some of the carcasses may have been consumed or carried away by scavengers, such as foxes and crows.…”
mentioning
confidence: 99%